Determinants and Variations of COVID-19 Vaccine Uptake and Responses Among Minority Ethnic Groups in Amsterdam, the Netherlands - Antwi-Berko, Daniel; Bakuri, Amisah Zenabu; Otabil, Kenneth Bentum; Kwarteng, Alexander (Frontiers in Public Health, 2022)
The outbreak of the deadly novel coronavirus disease (COVID-19) has disrupted life worldwide in an unprecedented manner. Over the period, scientific breakthroughs have resulted in the rollout of many vaccination programmes to protect against the disease, reduce the fear and ease public health restrictions for lives to return to some normalcy. The aim of this study was to identify the factors responsible for COVID-19 vaccine acceptance or vaccine hesitancy and to develop a framework to improve vaccine uptake in the Ghanaian-Dutch, Afro and Hindustani Surinamese-Dutch communities in Amsterdam. Using a mixed method approach, this community-based cross-sectional survey recruited 160 respondents consisting of 57 Ghanaian-Dutch, 54 Afro Surinamese-Dutch and 49 Hindustani-Dutch residents in Amsterdam. Our findings showed that the choice of a vaccine as well as the likelihood of self-reported willingness to receive a vaccine is highly dependent on vaccine efficacy and safety. Available evidence of high vaccine effectiveness and safety could encourage about 41.3% of the respondents to accept the vaccine. Additionally, 69.6% of the respondents indicated their willingness to accept the vaccine when vaccine passports are made mandatory by the government. Other major factors that could drive the likelihood of accepting the COVID-19 vaccine include travel requirement for vaccination (28.3%), the safety/probability of only minor side effects (26.1%) and recommendation by family and friends (15.2%). The study therefore provides systematic evidence of factors associated with individual preferences toward COVID-19 vaccination. It demonstrates that the needs of each community are unique and specific interventional efforts are urgently needed to address concerns likely to be associated with vaccine hesitancy.